Guinea pig cytomegalovirus immediate-early transcription. - Yin, C Y (1990)
Guinea pig cytomegalovirus (GPCMV) immediate-early (IE) gene expression was analyzed. GPCMV IE RNA was defined as RNA obtained from GPCMV-infected guinea pig cells treated with cycloheximide for 1 h before infection and for 4 h postinfection. Mapping studies showed that GPCMV IE genes are located at several distinct sites on the GPCMV genome. A total of 17 GPCMV IE transcripts were identified, and 9 IE transcripts coded for by three specific regions of the genome (regions I, II, and III) were characterized in detail. A series of recombinant DNA clones were generated to identify the nine IE transcripts. Three of the IE transcripts from region I and three from region III were transcribed in the same direction from overlapping sequences. The 2.0-kilobase (kb) transcript encoded by the EcoRI E DNA fragment (region II) was the most abundant IE GPCMV transcript. The cloned GPCMV DNA subfragment that was used to identify the region II EcoRI E 2.0-kb transcript did not hybridize to GPCMV early or late RNA, indicating that this transcript is expressed only under IE conditions. Expression of RNAs from the IE genes was also measured during a natural GPCMV infection in the absence of cycloheximide. During the natural infection, the transcripts previously identified under IE cycloheximide block conditions were expressed, and the region II EcoRI E 2.0-kb transcript was the most abundant transcript at 1 h postinfection. In addition, a rise and fall in RNA levels was observed during the natural infection, demonstrating the transient nature of expression of these transcripts. We conclude that GPCMV IE gene expression is complex, involving a reasonably large number of genes, and demonstrates some similarities with IE transcription by other CMVs.